The emerging landscape of circular RNAs in immunity: breakthroughs and challenges - Zhouxiao Li (Biomarker Research, 2020)
Abstract Circular RNAs (circRNAs) are covalently linked RNAs that exhibit individual strand with a closed-loop framework compared with a conserving, steady and abundant linear counterpart. In recent years, as high-throughput sequencing advancement has been developing, functional circRNAs have been increasingly recognized, and more extensive analyses expounded their effect on different diseases. However, the study on the function of circRNAs in the immune system remains insufficient. This study discusses the basic principles of circRNAs regulation and the systems involved in physiology-related and pathology-related processes. The effect of circRNAs on immune regulation is elucidated. The ongoing development of circRNAs and basic immunology has multiplied their potential in treating diseases. Such perspective will summarize the status and effect of circRNAs on various immune cells in cancer, autoimmune diseases and infections. Moreover, this study will primarily expound the system of circRNAs in T lymphocytes, macrophages and other immune cells, which creates a novel perspective and lay a theoretical basis for treating diseases.